Pelatihan Peningkatan Kompetensi Guru dalam Membuat Media Pembelajaran Berbasis IT di SMP Muhammadiyah Palangka Raya: Training for Increasing Teachers' Competence in Making IT-Based Learning Media at SMP Palangka Raya Muhammadiyah - Nurul Hikmah; Surawan Surawan; Muhammad Redha Ansari; Endah Endah; Muslimah Muslimah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Based on the results of observations and interviews with the principal, data was obtained that even though the learning process had been carried out for approximately four semesters online or online. However, SMP Muhammadiyah Palangka Raya teachers still have not followed developments in using IT-based learning media. During this time, the learning process is carried out using the WhatsApp group. Therefore, the principal wants training to increase teacher competence in making IT-based learning media. In particular, the creation and use of google classroom and google class meet as learning media. This study aimed to determine teachers' competence in making IT-based learning media at SMP Muhammadiyah Palangka Raya before and after service activities. This activity uses lecture, demonstration, discussion, question and answer, practice, and guidance methods. The activity results show an increase in teacher competence in making IT-based learning media at SMP Muhammadiyah Palangka Raya, especially in the creation and use of google classroom and google meet as learning media.